Bacterial infective arthritis of the coxofemoral joint in dogs with hip dysplasia - Benzioni, H.; Shahar, R.; Yudelevitch, S.; Milgram, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
The objective of this study was to describe seven cases of unilateral bacterial infective coxarthritis from a total of 19 cases of bacterial infective arthritis (BIA), presenting over a two year period. We recorded the history, clinical signs, diagnostic process, treatment and clinical outcome in these cases. The data were obtained from medical records, review of the radiographs, and telephone follow-up with the owners. All of the dogs in this study had severe chronic osteoarthritis secondary to hip dysplasia, which caused periodic hind limb lameness. They were all admitted with severe acute hind-limb lameness. Pelvic radiographs were performed under general anaesthesia shortly after presentation, followed immediately by arthrocentesis of the affected joint. The synovial fluid was evaluated microscopically by direct smear and a sample was sent for culture and sensitivity. An attempt was not made to drain or lavage the affected joint during the course of treatment. The initial choice of antibiotics was empiric and subsequently modified, as required, based on the sensitivity results. Four of the dogs showed a rapid return to weight-bearing after the initiation of antibiotic treatment, and all of the patients returned to their pre-BIA level of function. Neither recurrent infections nor any adverse sequela requiring further intervention were reported by the owners on telephone follow-up.
Keywords: Bacterial infective arthritis; arthrocentesis; coxofemoral joint; canine hip dysplasia; dogs